New species of Heteropsilopus and Amblypsilopus from China (Diptera: Dolichopodidae) - Liu, Xiaoyan; Zhu, Yajun; Yang, Ding (Zootaxa, 2012)
Heteropsilopus, previously believed to be restricted to southern Australia, south-western India and Sri Lanka, is reported from China for the first time. Two species, Heteropsilopus yunnanensis sp. nov. and Amblypsilopus curvus sp. nov., are described as new to science. The latter belongs to the Amblypsilopus flaviappendiculatus group.